A study of clinical and ophthalmologic profile of patients undergoing cataract surgery - Shori, Chhaya; Shori, Rakesh; Laxmiprasad, Gannaram; Alli, Ashalatha (International Journal of Research in Medical Sciences, 2017)
Background: Intraocular lens implantation is the only surgical approach available mostly in developing countries. Thus cataract constitutes as the leading cause of blindness in developing countries as many patients with cataract do not have access to hospitals and surgery. Objective was to study the clinical and ophthalmologic profile of patients undergoing cataract surgery. Methods: A hospital based cross sectional study was carried out among 100 cataract patients assigned to undergo conventional extra capsular cataract excision surgery for a period of two years in a tertiary care referral hospital. One day before the surgery these patients were admitted to the indoor wards of department of ophthalmology. From each patient, detailed history was obtained. Visual acuity was checked with Snellen’s visual acuity chart and pinhole improvement was noted. Results: Maximum prevalence was seen in the age group of 51-60 years i.e. 37% followed by 61-70 years of 30%. Thus cataract is seen more commonly in the age group of above 50 years. Prevalence of cataract was more in females (59%) as compared to 41% in males. Cortical cataract constituted 86% of total cases and remaining 14% were constituted by nuclear type of cataract. Majority of the patients i.e. 59% had visual acuity of less than 1/60 followed by 33% of having 5/60 to 1/60. 58% of the patients had against the rule type of astigmatism. 34% of the patients had with the rule type of astigmatism. Only 8% had NOA type of astigmatism. Conclusions: Increasing age and female gender were the most important risk factors in the present study. Cortical type of cataract was more common than nuclear type of cataract. Maximum had low vision.